Pergeseran Sifat Konfessionalitas Pendidikan Nasional Indonesia - Furqon, Arief (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
This research is to describe the change of characteristics of national education which is secular to be confessional, it starts from the independence until this time. This change will be known from the changing of the aim of national education which is as mirror of nation needed to make the ideal which is needed as a result of the education. According to the result of research, it can be concluded that national education, step by step gets changing from the secular to be confession. As the consequence, the position of religion education in structure of national education getschanging from the marginal position to central position, it becames one of the field that should be given to all strata's, types and ways of education in Indonesia.